INDUCED BREAST CANCER IN A MAN WITH MULTIPLE PRIMARY CANCER (A CASE REPORT) - А. D. Kaprin; А. D. Zikiryakhodzhaev; Е. V. Tyshchenko; А. S. Sukhotko (Сибирский онкологический журнал)
A case report of polyneoplasia in a male patient with induced breast cancer demonstrates current trends in drug therapy for multiple primary cancers.